Identitas nasional sebagai karakter bangsa indonesia dalam bermedia sosial: Antara tantangan dan tanggung jawab negara - Ramadhani, Ainiyya (Maliki Interdisciplinary Journal, 2025)
This article discusses the urgency of Indonesian national identity in the era of ever-growing digital globalization. Amidst the unlimited flow of global information and culture, social media has become a major driving force that significantly influences the character and image of the nation. However, unwise use of social media has the potential to erode the noble values ​​and norms of national identity. Using a qualitative descriptive-analytical method, this study aims to explain the meaning of national identity in the context of the digital era and analyze the social media behavior of Indonesian people in relation to national character. This article offers concrete solutions to build a social media culture that reflects and strengthens national identity. The discussion includes the concept of national identity based on Pancasila, Bhinneka Tunggal Ika, language, culture, and history, as well as the dynamics of social media use in Indonesia which shows wide penetration with the dominance of entertainment content. Challenges such as disinformation, hate speech, and instant culture are discussed as threats to national values. Therefore, the strategy for strengthening national identity involves digital citizenship education, the role of influencers and content creators, and individual responsibility as netizens.